2008
DOI: 10.1128/jvi.01930-07
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Responses of Pseudomonas aeruginosa to Phage PRR1 Infection

Abstract: The infectious cycles of viruses are known to cause dramatic changes to host cell function. The development of microarray technology has provided means to monitor host cell responses to viral infection at the level of global changes in mRNA levels. We have applied this methodology to investigate gene expression changes caused by a small, icosahedral, single-stranded-RNA phage, PRR1 (a member of the Leviviridae family), on its host, Pseudomonas aeruginosa, at different times during its growth cycle. Viral infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 37 publications
2
37
0
1
Order By: Relevance
“…Interestingly, it was evidenced that the chaperonin GroEL and the elongation factor EF-Ts were upregulated in response to virus challenge. Molecular chaperones, including the heat shock proteins, are a ubiquitous feature of cells, in which these proteins cope with stress-induced denaturation of other proteins (19,20). In this report, a molecular chaperonin, GroEL, was revealed to be involved in GVE2 infection.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Interestingly, it was evidenced that the chaperonin GroEL and the elongation factor EF-Ts were upregulated in response to virus challenge. Molecular chaperones, including the heat shock proteins, are a ubiquitous feature of cells, in which these proteins cope with stress-induced denaturation of other proteins (19,20). In this report, a molecular chaperonin, GroEL, was revealed to be involved in GVE2 infection.…”
Section: Discussionmentioning
confidence: 89%
“…There is an increasing body of knowledge regarding bacteriophage-host interactions, as well as molecular aspects of bacteriophages, in particular, the host stress response proteins and the proteins induced by bacteriophages. With the accumulated data, it was found that the process of bacteriophage-host interaction requires the actions of the most highly induced genes encoding chaperones and other stress-inducible proteins (19,20). Previous studies have revealed that bacteriophage infection is actually dependent on several cellular chaperonins, proteases, ABC transporters, and other heat shock regulons (17,19).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Whole-genome transcriptomics studies have shown that host transcription shutdown or reprogramming is by no means a universal feature of bacteriophage infection (10)(11)(12)(13)(14). The majority of these studies, undertaken in E. coli, P. aeruginosa, Lactococcus lactis, and the archaeon Sulfolobus solfataricus¸have revealed a remarkably small effect of phage infection on host transcriptomes, with more-pronounced changes occurring only during late infection and usually involving increased transcription of stress response-associated genes.…”
mentioning
confidence: 99%